2010
DOI: 10.1254/jphs.10094fp
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin 2C Receptor (5-HT2CR) mRNA Editing–Induced Down-Regulation of 5-HT2CR Function in Xenopus Oocytes: the Significance of Site C Editing

Abstract: Abstract. Serotonin 2C receptor (5-HT2CR) mRNA receives editing at 5 nucleotide positions (sites A -E) located in the sequence encoding the second intracellular loop of 5-HT2CR. 5-HT2CR mRNA without editing and with editing at sites AB, ABD, ABC, ABCD, and C are translated to 6 isoforms of 5-HT2CR: INI(non-edited), VNI(AB), VNV(ABD), VSI(ABC), VSV(ABCD), and ISI(C), respectively. In this study, we investigated electrophysiologically the ability of these isoforms to couple with the G protein / phospholipase C (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Similarly, editing efficiency at sites A, B, E, C, and D (analyzed as repeated measures) was lower in MDD NoSuic compared with two other groups. In contrast, the frequencies of the nonedited ( NONE ) variant and the AD variant that encode high-functioning receptor isoforms (Niswender et al 1999; Wang et al 2000b; Tohda et al 2010) were higher in MDD NoSuic than in NC or MDD Suic (Figure 3). There were no significant differences between NC and MDD Suic .…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…Similarly, editing efficiency at sites A, B, E, C, and D (analyzed as repeated measures) was lower in MDD NoSuic compared with two other groups. In contrast, the frequencies of the nonedited ( NONE ) variant and the AD variant that encode high-functioning receptor isoforms (Niswender et al 1999; Wang et al 2000b; Tohda et al 2010) were higher in MDD NoSuic than in NC or MDD Suic (Figure 3). There were no significant differences between NC and MDD Suic .…”
Section: Resultsmentioning
confidence: 95%
“…Specifically, the sum of frequencies of all transcripts edited at the E or C sites, and the frequency of the most abundant mRNA variant, ABCD (Figure 3), which collectively represent a population of the low-functioning receptor isoforms (Niswender et al 1999; Wang et al 2000b; Tohda et al 2010), were lower in MDD NoSuic compared with NC and MDD Suic . Similarly, editing efficiency at sites A, B, E, C, and D (analyzed as repeated measures) was lower in MDD NoSuic compared with two other groups.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on these observations, it may be hypothesized that some of the factors produced by the 5-HT2CR mRNA at day 15 serve physiological roles at the moment of synaptogenesis. Many reports have mentioned the various phenomena of 5-HT2CR mRNA, including the short variant of RNA [7,17], the generation of the 95-nt fragment from the 5-HT2CR mRNA [17], the existence of the binding site for MBII-52 (a type of small RNA) [18], and the functional regulation of 5-HT2CR activity via RNA editing [19]. The 5-HT2CR mRNA product may serve an important function during the synaptic joining.…”
Section: Discussionmentioning
confidence: 99%
“…Among 5 editing sites, the editing frequencies at the A and B sites are kept low in the rat brain during fetal development, but these are approximately completely edited from just after birth (29). Under full editing of the A/B site, namely, in the brain after birth, it is suggested that editing of the C site decides the strength of the 5-HT2C signal (30).…”
Section: Rna Editing (Fig 1)mentioning
confidence: 99%